A PANEL STUDY OF CORPORATE VENTURING AND LISTED MANUFACTURING FIRMS’ GROWTH IN NIGERIA - Ayorinde, Afisat Abolore; Adeyeye, Mercy Modupe; Sajuyigbe, Ademola Samuel; Omoshagba, Praise Oluwatoyin (APPS Publications, 2021)
The study sought to investigate the impact of corporate venturing dimensions on organisational growth with specific reference to consumer goods manufacturing firms listed by the Nigerian Stock Exchange (NSE). The populace for the study comprised the twenty-one (21) listed consumer goods manufacturing companies in Nigeria as of January 2020 out of which fifteen (15) companies were used as sample size based on inclusion and exclusion criteria. A panel study was conducted using ten years (2010-2019) published and audited annual accounts. Pearson-Moment Correlation Coefficient and Linear Regression were used for the evaluation. The result exhibits a positive correlation between internal corporate venturing, external corporate venturing, cooperative corporate venturing, and organisational growth. The study supports the preceding studies that investment in corporate venturing is an alternative paradigm to organizational growth. Therefore, the study encouraged that manufacturing companies should invest judiciously on corporate venturing. Thus, will go a long way for the sector to take a leading position in economic activities.